Melek Digital: Melawan Hoaks Dan Konten Toxic - Fian Hidayatulloh; Rahman Hakim Budiman; Septyana Wulansari (CV. ITTC INDONESIA, 2025)
In today’s rapidly evolving digital era, students are required to possess digital literacy skills to navigate the overwhelming flow of information, which is not always accurate. This community service program (PKM) was conducted at SMA Negeri 6 Tangerang Selatan, aiming to enhance students’ digital literacy, particularly in recognizing and combating hoaxes and toxic content. The implementation employed an interactive counseling and mentoring approach through discussions, hoax identification simulations, and positive digital campaigns. The results indicated a significant improvement in students’ understanding of information verification, digital ethics, and responsible online behavior. The program successfully fostered ethical awareness and critical thinking among students, promoting a healthy and productive digital environment.